Visible-light-driven photocatalytic performance of nanohybrid incorporating nickel ions into the tetratitanate interlayer. (April 2017) - He, Liwen; Liu, Hong; Lv, Bingjie; Liu, Peide; Lin, Bizhou
Abstract: Ni-intercalated tetratitanate with a Ni:Ti molar ratio of 1:6.3 was prepared by electrostatically-driven self-assembly of the negatively charged exfoliated nanosheets and the positively charged nickel ions. The introduction of Ni 2+ makes the doped titanate to possess spectral responses to visible light, contributed by the hybridization of the 3d orbits of Ni and Ti in the conduction band. The as-prepared materials exhibit mesoporous textures with expanded specific surface areas of more than 90 m 2 /g and highly photocatalytic activities in the degradation of methylene blue under visible-light irradiation. Highlights: Assembly of the negatively charged exfoliated tetratitanate nanosheets and Ni 2+ ions. High Ni 2+ dopant narrowed the band gap by hybridizing 3d orbits of Ni and Ti. The doped titanates exhibited highly visible-light-driven photocatalytic activities.